Abiotic Factors Modulating Metabolite Composition in Brown Algae (Phaeophyceae): Ecological Impacts and Opportunities for Bioprospecting of Bioactive Compounds - Lopes, Clara; Obando, Johana Marcela Concha [UNESP]; Santos, Thalisia Cunha dos [UNESP]; Cavalcanti, Diana Negrão; Teixeira, Valéria Laneuville (MDPI, 2024)
Brown algae are vital structural elements and contributors to biodiversity in marine ecosystems. These organisms adapt to various environmental challenges by producing primary and secondary metabolites crucial for their survival, defense, and resilience. Besides their ecological role, these diverse metabolites have potential for biotechnological applications in industries including pharmaceuticals, cosmetics, and food. A literature review was conducted encompassing studies from 2014–2024, evaluating the effects of hydrodynamics, temperature, light, nutrients, seasonality, and salinity on the chemical profiles of various Phaeophyceae algae species. Thirty original articles spanning 69 species from the Sargassaceae, Dictyotaceae, Fucaceae, and Scytosiphonaceae families were analyzed and systematically arranged, with a focus on methodologies and key findings. This review furthers ecological discussions on each environmental factor and explores the biotechnological potential of metabolites such as polysaccharides, fatty acids, phenolics, diterpenes, and pigments. The information in this work is beneficial for metabolite bioprospecting and in vitro cultivation models as well as indoor and outdoor cultivation studies.
Keywords: abiotic parameters; brown seaweed; natural products; Phaeophyceae